ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA PEMERINTAH DAERAH KABUPATEN ROKAN HULU - Nurhayati (Jurnal Ilmiah Cano Ekonomos, 2014)
This study aims to provide information to the public regarding the presentation of the goverment’s performance in achieving accountability. To determine the performance of RokanHulu district goverments using financial ratios budget especially the ratio of local independence, the ratio the area of financial dependence, the ratio of effectiveness, efficiency ratio, the ratio of the ratio of the activity, the ratio of growth. Financial ratio analysis on revenue and expenditure budget for the 2009-2012 fiscal yaer as measured by ratio of local independence is very low, the ratio the area of financial dependence is very high, the ratio effectiveness of the fiscal year 2009-2012 is very effective while the effeciency ratio of the fiscal year 2009-2012 is very efficient, the ratio of the activity of the fiscal 2009-2012 which explains that the results routine spending is prioritized ratio compared to the ratio of development expenditure,and ratio of growth to ain increase in local revenues that fluctuate from year 2009-2012.